Local and trans-local dynamics of innovation practices in the Taipei design industry: an evolutionary perspective. Issue 7 (3rd July 2018) - Lin, Cheng-Yi
ABSTRACT: Spatial-organizational proximities are crucial elements underpinning the innovation practices of creative industries. However, few studies have systematically explored how creative industries integrate the heterogeneous synergies of local and trans-local innovation practices as the diversity driving the evolution of a creative cluster within an Asian city. This paper contributes to unpacking the spatiality of local and trans-local innovation practices in the design industry from an evolutionary perspective. Based on 55 semi-structured interviews with Taipei product designers from 2011 to 2015, this paper presents a multi-dimensional framework for the spatiality of innovation practices, which exhibit two evolutionary dynamics in Taipei's design industry cluster. First, the political-economic context enables the design industry to recombine heterogeneous knowledge by illustrating different proximities and diversities in various spatial-temporal environments. Second, the design industry increasingly depends on local and trans-local innovation practices, leading to a dynamic spatial strategy of design product differentiation. Studying the spatiality of innovation practices in the design industry reveals that the role of strategic agency, not spatial conditions, is crucial to understanding the transformation of the design economy.